PROSPEK KEPARIWISATAAN DAN DAYA TARIK DAERAH TUJUAN WISATA - Saputro, Edy Purwo; Nurdiana, Fereshti; Cahyono, Yuli Tri (Benefit: Jurnal Manajemen dan Bisnis, 2006)
Tourism sector represent important component in economics. Tourism sector development basicallyrepresent reference to see how big potency which can give benefit, not even in the case of acceptance state -area, but also aspect absorption and labour repair prosperity society systematically. Tourism sectorpotency Indonesia that owns of a number of tourism assets, especially cultural tourism. This assettourism characteristic indirectly exactly becomes distinguishing factor with other area. Therefore, needthere systematic sale pattern to support tourism potency.